Formulation and Characterization of Solid Dispersions of Glimepiride through Factorial Design: Formulation and characterization of glimepiride - Veerendra S. Rajpurohit; Pankaj Rakha; Surender Goyal; Harish Dureja; Gitika Arorac and Manju Nagpal (Iranian Journal of Pharmaceutical Sciences, 2011)
In order to enhance in vitro dissolution and content uniformity of poorly soluble drug glimepiride by preparing solid dispersions using modified solvent fusion method, solid dispersions of drug were prepared by modified fusion solvent method using PEG 6000 and PVP K25 (as carrier). Eight batches (F1-F8) were prepared by Factorial design (23) by taking three factors i.e. the concentration of: drug (X1), PEG 6000 (X2) and PVP K25 (X3). DSC, FTIR spectroscopy, powder X-ray diffraction (XRD) and SEM studies were used to characterize solid dispersions. In vitro release was carried out using USP II dissolution apparatus. Multilinear regression analysis was applied to develop mathematical model to estimate cumulative drug release. The batch F3 was found to be best batch as it showed maximum in vitro dissolution after 30 min. Improvement in dissolution behavior of solid dispersion batches was observed due to conversion of crystalline form of drug to amorphous form as confirmed by DSC, FTIR studies and X-RD studies. SEM photographs of batch F3 showed porous nature of particle surface. Uniformity of content of different batches was found to be in range as specified by IP. Solid dispersion prepared via modified fusion solvent method was proved to be beneficial in enhancement of dissolution rate of poorly-water soluble drug using hydrophilic carriers. Retrospectively, this model can further be utilized to design solid dispersions for desired release characteristics.